Enzymatic extraction and characterisation of melanosomes from human hair - Ng, Hui Min (2016)
Melanins are major pigments that are present in skin, hair and eyes of humans and animals. Numerous researches was done on melanosomes, however, current understanding of its physical and chemical properties are still limited. Melanin has many unique features which have the capability to be applicable in our lives.